2002
DOI: 10.1007/bf03404549
|View full text |Cite
|
Sign up to set email alerts
|

Refusals and Delay of Immunization Within Southwest Alberta

Abstract: Background: Immunization is a necessary component of well child services within public health. Despite the documented effectiveness of vaccines, some parents choose to refuse or delay immunization for their children. Adherence to different beliefs has affected immunization coverage in one Regional Health Authority in Southwest Alberta. Methods: This qualitative study involved exploratory, descriptive open-ended interviews with a sample of 47. The sample included people of Dutch ethnic background, Hutterites, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 8 publications
1
5
0
1
Order By: Relevance
“…Additionally, approximately one third (33%) of parents who do not vaccinate their children cite religious or philosophical reasons (Gilbert et al 2017), which may further contribute to the low vaccination rates in some rural communities (Bell et al 2015). Even though there are only a few studies in this review examining these factors, these findings are consistent with studies showing that vaccine hesitancy is related to alternative medicine practices (DubĂ© et al 2016b ;DubĂ© et al 2013;Frawley et al 2018;McNeil et al 2019) and religious beliefs in Canada (DubĂ© et al 2018;Kulig et al 2002) and elsewhere in the world (Kershaw et al 2014;Rainey et al 2011;SAGE Working Group 2014;Spaan et al 2017).…”
Section: Discussionsupporting
confidence: 69%
“…Additionally, approximately one third (33%) of parents who do not vaccinate their children cite religious or philosophical reasons (Gilbert et al 2017), which may further contribute to the low vaccination rates in some rural communities (Bell et al 2015). Even though there are only a few studies in this review examining these factors, these findings are consistent with studies showing that vaccine hesitancy is related to alternative medicine practices (DubĂ© et al 2016b ;DubĂ© et al 2013;Frawley et al 2018;McNeil et al 2019) and religious beliefs in Canada (DubĂ© et al 2018;Kulig et al 2002) and elsewhere in the world (Kershaw et al 2014;Rainey et al 2011;SAGE Working Group 2014;Spaan et al 2017).…”
Section: Discussionsupporting
confidence: 69%
“…These findings are in line with the results of previous research showing that orthodox protestant youngsters in the Netherlands were far more interested in the religious aspects of vaccination than in the medical aspects [ 26 ]. In a Canadian study on refusal of immunization, it was also reported that for Dutch immigrants (belonging to religious congregations related to the denominations described here) religious arguments were decisive [ 27 ]. However, in both these studies orthodox Protestants who accepted vaccination were not included.…”
Section: Discussionmentioning
confidence: 99%
“…Some respondents also cited religion as a reason for refusal, stating that certain religious organizations actively discourage vaccinations among its members. Kulig, Meyer, Hill, Handley, Lichtenberger, and Myck [18] did a similar study but in the Nigerian setting and they discovered that Muslim mothers made up the majority of respondents who opted not to have their children immunized. Religion was also seen as the main factor for the decision of these mothers in Nigeria.…”
Section: Reasons For Child Immunization Refusal Among Parentsmentioning
confidence: 94%